Suriname : 2004 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Suriname. (IMF Staff Country Reports; Country Report ;, 2005)
This 2004 Article IV Consultation highlights that tighter fiscal and monetary policies in Suriname helped stabilize the exchange rate and moderate inflation pressures in 2003 and 2004. The fiscal deficit narrowed from 6.5 percent of GDP in 2002 to near balance in 2003, while a tighter monetary policy helped to reduce inflation from 28 percent in 2002 to 13 percent in 2003. The financial system has become increasingly dollarized in recent years, reflecting the lingering effects on confidence of earlier episodes of price instability, as well as regulatory changes favoring foreign currency intermediation.